Teaching English through task and project-based learning to Embera Chamí students - Rojas, Luis Ricardo; Rueda Varon, Jenifer (Colombian Applied Linguistics Journal, 2019)
Bilingual indigenous students who attend public schools around the country are to develop English language skills as part of the suggested curriculum created by the Colombian Ministry of Education. This is the case of the Embera Chamí students in Florencia, Caquetá whose conditions for learning English differ from those of monolingual Spanish students. The purpose of this study is to analyze the difficulties and the advantages of learning English through task- and project-based learning in bilingual indigenous students. The analysis of the study was developed through the method of systematization of experience. Results suggest that the two learning approaches enhanced indigenous students’ speaking skills and facilitated vocabulary recognition. However, the students mentioned being more interesting in learning English for specific purposes.